The Wick Effect and Its Impact on Ignition Conditions for Liquid and Solid Organic Substances: Methodological Recommendations for Forensic Practitioners - I. S. Taubkin (Теория и практика судебной экспертизы)
The paper examines conditions for the ignition of high fire point combustible liquids on extended surface materials (e.g. textiles or insulating materials) prone to the so-called «wick effect». It is demonstrated that such liquids may ignite at lower temperatures than their standard fire points. The «wick effect» has to be taken into account when determining the nature of the liquid used to set fire to a person and/or property. The implications of this effect for the spontaneous combustion of liquids and meltable solid organic substances on porous materials is also discussed.ERRATUMAn error was discovered in the article. The reference to GOST R 51355-99 on page 47 was incorrect and should have read as follows: Alekseyev S.G., Barbin N.M., Avdeyev A.S., Pishchal’nikov A.V. Explosion and Fire Hazards of Vodka. Fire and Explosion Safety. 2009, vol. 18, No 2, pp. 20–23. The error was corrected on April 6, 2018.